Spatial contrast sensitivity of migraine patients without aura - Benedek, K; Tajti, J; Janáky, M; Vécsei, L; Benedek, G (Cephalalgia, 2002)
Visual disturbances are frequent symptoms in migraine. Since there is a possibility of separate damage in the magno- or parvo-cellular visual pathway in migraine patients, we performed a study including the measurement of static and dynamic spatial contrast sensitivity on 15 patients suffering from migraine without aura under photopic and scotopic conditions. Fifteen healthy volunteers without primary headache served as controls. The results revealed a marked decrease in contrast sensitivity at low spatial frequencies in the migraine patients. Spatial contrast sensitivity demonstrated some lateralization, as the sensitivity to low spatial frequencies obtained through separate eyes showed significantly larger side-differences in migraine patients than in control subjects. These findings suggest that the mechanisms responsible for vision at low spatial frequencies are impaired in migraine patients. This might indicate impaired function of the magnocellular pathways in this condition.